Does low back pain affect the reliability of postural regulation?. (3rd April 2019) - Lauenroth, Andreas; Reinhardt, Lars; Schulze, Stephan; Laudner, Kevin G.; Delank, Karl-Stefan; Schwesig, René
Abstract: The aim of this study was to examine the intraobserver reliability of a posturographic assessment in patients with low back pain. We investigated 24 symptomatic subjects with defined low back pain (mean: 57.9 years) and a pair-matched control group including 24 asymptomatic persons (mean: 58.1 years). Each participant underwent two measurements on a posturographic device (32 Hz sampling rate) based on the Interactive Balance System (time interval: 7 d). Test procedure consisted of tests on solid ground with eyes open (1) and eyes closed (2). Data analysis included parameters of motor output and a frequency band analysis. Reliability tests were realized using by intraclass correlations (ICC). Coefficients of ICC ranged from 0.36 (95% CI: 0.01–0.73) to 0.94 (95% CI: 0.86–0.97) in both test positions. For 69% (11/16) of the investigated parameters a high level (ICC > 0.75) of intraobserver reliability was reached. Based on the results, the posturographic measurement system used in this study seems to be appropriate for use in longitudinal study designs in an orthopaedic setting.